Crack path in aeronautical titanium alloy under ultrasonic torsion loading (Fracture and Structural Integrity, 2015)
This paper discusses features of fatigue crack initiation and growth in aeronautical VT3-1 titanium alloy under pure torsion loading in gigacycle regime. Two materials: extruded and forged VT3-1 titanium alloys were studied. Torsion fatigue tests were performed up to fatigue life of 109 cycles. The results of the torsion tests were compared with previously obtained results under fully reversed axial loading on the same alloys. It has been shown that independently on production process as surface as well subsurface crack initiation may appear under ultrasonic torsion loading despite the maximum stress amplitude located at the specimen surface. In the case of surface crack initiation, a scenario of crack initiation and growth is similar to HCF regime except an additional possibility for internal crack branching. In the case of subsurface crack, the initiation site is located below the specimen surface (about 200 µm) and is not clearly related to any material flaw. Internal crack initiation is produced by shear stress in maximum shear plane and early crack growth is in Mode II. Crack branching is limited in the case of internal crack initiation compared to surface one. A typical ‘fish-eye’ crack can be observed at the torsion fracture surface, but mechanism of crack initiation seems not to be the same than under axial fatigue loading.
Keywords: Very-High Cycle Fatigue; Titanium alloy; Ultrasonic; Crack growth